Multimodal and multiscale characterization of bone and bone interfaces in health and disease - Micheletti, Chiara (My University, 2023)
Seeing is believing. Our understanding of phenomena often involves their direct observation. However, bone architecture is challenging to visualize given its multi-level hierarchical organization. In this thesis, bone and bone interfaces are characterized via multimodal and multiscale platforms, combining different techniques across several length scales. Imaging techniques across the micro-nano continuum are complemented by spectroscopy methods to explore, respectively, the structure and composition of bone and bone interfaces, using both light and electron probes. By applying a characterization methodology more typical of materials science, this thesis aims to unveil structural and compositional abnormalities of bone induced by disease [Papers I-II], and bone response to functionalized biomaterials in compromised conditions [Papers III-IV]. Additionally, it expands three-dimensional (3D) characterization opportunities at the nanoscale in both native and peri-implant bone [Papers V-VI]. This characterization approach uncovered changes in bone quality (structure and/or composition) in the compromised conditions under investigation in this thesis, i.e., leptin receptor (LepR) deficiency and medication-related osteonecrosis of the jaw (MRONJ) [Papers I-II]. In a preclinical model of LepR deficiency for type 2 diabetes/obesity, multimodal characterization of bone at the microscale showed structural abnormalities indicative of delayed skeletal development, despite unaffected bone matrix composition [Paper I]. A combination of multiscale imaging and spectroscopy techniques spanning the micro-to-nanoscale enabled a detailed study of the interface between necrotic bone and bacteria in a case of MRONJ, shedding light on possible mechanisms of bone degradation. When applied to bone-biomaterial interfaces, the application of a multimodal and multiscale characterization workflow informed perspectives on bone response to novel biomaterial solutions aimed to promote osseointegration in osteoporotic conditions via local drug delivery of phytoestrogens [Paper III] or anabolic agents [Paper IV]. This highlighted the importance of studying peri-implant bone at the mesoscale [Paper III] and of confirming biomaterial behaviour in vivo in the presence of surface functionalization [Paper IV]. Lastly, this thesis emphasized the importance of 3D imaging at the nanoscale with electron tomography to resolve bone ultrastructure at biomaterial interfaces [Paper V] and in native conditions [Paper VI]. Specifically, in Paper VI, artifact-free on-axis electron tomography resolved some long-debated aspects regarding the organization of mineralized collagen fibrils, the fundamental building block units of bone.
Thesis in cotutelle with the University of Gothenburg, Department of Biomaterials, Institute of Clinical Sciences, Sahlgrenska Academy Gothenburg, Sweden
Keywords: bone; osseointegration; characterization